STRATEGI PENGELOLAAN KELAS DALAM PROSES PEMBELAJARAN - Abu Hasan Agus R (Nurul Jadid University, 2015)
Classroom management is a combination of two words ie words and word-class management. Management in English termed Management, Management of Understanding management or in general, ie activities include planning, organizing, directing, coordinating, monitoring, and assessment.Classroom management (Management of classroom) is a series of actions taken in order to create a learning environment that is positive and productive learning so that the learning process to be run in accordance with its purpose. In other words, classroom management is empowering potential of the class through a set of learner skills intuk create conducive learning environment, positive, and productive and to control if an interruption in learning to optimize the learning process so as to obtain satisfactory results.